2010
DOI: 10.5032/jae.2010.04105
|View full text |Cite
|
Sign up to set email alerts
|

Early Career Agriculture Teachers’ Efficacy Toward Teaching Students with Special Needs

Abstract: This study sought to assess the perceptions of early career agriculture teachers' ability to teach students with special needs. Agriculture teachers in the first five years of their careers indicated that administrative support contributed the most to their success in working with students with special needs, while in-service activities that focused on students with special needs contributed little. Self-efficacy was the strongest predictor of self-perceived success of teaching students with special needs. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Participants identified reliable administrative support as a condition of their success and longevity. This finding is strongly supported within our field (Hasselquist, et al, 2017;Aschenbrener, Garton, & Ross, 2010;Boone & Boone, 2009) and the relationship teachers develop with supportive administration. Historical analysis of existing data indicated negative relationships with administration are a significant contributor to teacher dissatisfaction (Perie & Baker, 1997).…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 81%
“…Participants identified reliable administrative support as a condition of their success and longevity. This finding is strongly supported within our field (Hasselquist, et al, 2017;Aschenbrener, Garton, & Ross, 2010;Boone & Boone, 2009) and the relationship teachers develop with supportive administration. Historical analysis of existing data indicated negative relationships with administration are a significant contributor to teacher dissatisfaction (Perie & Baker, 1997).…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 81%
“…The synthesis of data collected through three decades of SBAE needs assessment research confirmed that competency levels and priority areas of needs are diverse and somewhat inconsistent depending on the level of teaching experience (pre-service, novice, or experienced/senior teachers) and type of teacher certification (traditional or alternatively certified teachers). A contrast in needs was found among the competency areas, some of which included completing reports and forms, managing student behavior problems, preparing contest teams, locating adequate teaching materials, and conducting adult education programs (Aschenbrener et al, 2010;Birkenholz & Harbstreit, 1987;Claycomb & Petty, 1983;Drage, 2010;Duncan et al, 2006;Edwards & Briers, 1999;Garton & Chung, 1996;1997;Joerger, 2002;Layfield & Dobbins, 2002;Mundt & Connors, 1999;Roberts & Dyer, 2004;Sorensen et al, 2010;Sorensen et al, 2014;Touchstone, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Elbert and Baggett (2003), Duncan et al (2006) listed teaching learning disabled students as an in-service need in the category of Teaching and Learning. Aschenbrener, Garton, and Ross (2010) also reported adapting curriculum for students with disabilities, including students with disabilities in the mainstream, keeping students on task, and working with special education teachers were of high development need. Sorensen et al (2010) mentioned teaching students with disabilities was one of the top three highest ranked needs in Utah.…”
Section: Needs Assessments For Sbae Teachers From 2000 To 2015mentioning
confidence: 99%
“…While this finding is inconsistent with many other studies on regards to overall perceptions (Boone, Watts, Boone & Gartin, 2008;Elbert & Baggett, 2003;Kessell, 2005). Aschenbrener, Garton and Ross (2010) also found that early career agriculture teachers expressed some confidence in working with students with special needs. This overall confidence is a positive step, not only for successful inclusion, but for overall teacher career efficacy and satisfaction.…”
Section: Discussionmentioning
confidence: 92%